Haemostatic properties of Vernonia amygdalina and Chromolaena odorata leaf extracts using Wistar rat model - Matthew, Lucy Omokhegbe; Osime, Evarista Odaburhine (Faculty of Medicine, Trisakti University, 2019)
BACKGROUNDThe leaves of African plants are widely employed in Nigeria to control bleeding from wounds. This work is aimed at evaluating the haemostatic effects of Vernonia amygdalina (VA/bitter leaf) and Chromolaena odorata (CO/sunflower) leaves on some haemostatic parameters.METHODSA laboratory study of experimental design was conducted involving 35 Wistar rats that were randomized into seven groups. Groups 1 and 2 received leaf extracts of VA at concentrations of 150 and 250mg/kg BW, respectively; groups 3 and 4 received leaf extracts of CO at 150 and 250mg/kg BW; groups 5 and 6 received combined leaf extracts of VA and CO at 150 and 250mg/kg BW, respectively, for 30 days. The last group 7 as control group received only water. Parameters investigated were clotting time (CT), fibrinogen concentration, prothrombin time (PT), activated partial thromboplastin time test (APTT), factor VII, protein C and D – dimer.ResultsThere was a significant reduction in CT, fibrinogen concentration and PT in the intervention groups compared to controls (p<0.01). There was no significant difference in APTT, factor VII and protein C in the intervention groups compared to the controls (p>0.05). D-dimer levels were observed to increase significantly in rats treated with 150mg/kg BW of VA and 150mg/kgBW of the combined leaf extracts (VA/CO) compared to the controls (p<0.05).ConclusionThe VA and CO extracts reduced CT, PT, fibrinogen concentrations and increased D-dimer levels in rats. This study suggests the possible incorporation of the leave extracts of VA and CO in bleeding diathesis as well as in coagulation studies.